(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This research aims to show how important the total access to the internet signal is, and even in the face of the end of the data package, the signal should be released to these people, as an exchange of knowledge and information. For this, the research will be qualitative-bibliographical, through the access to the internet database, when surveying scientific-legal articles related to the proposed theme. It is also important to mention the bibliographical survey of works related to the theme. Is restricting the access to the internet signal because the data package runs out a violation of the ban on retrogression? This research concludes on the retrocession in imposing the purchase of new packages, before the essentiality of the internet signal and the need of students and workers for unrestricted and fundamental access in the Information Society.